A Combinatorial Investigation of Fe-Si-Zn Thin Film Negative Electrodes for Li-Ion Batteries. Issue 1 (1st January 2015) - MacEachern, L.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Thin-film Fe-Si-Zn libraries were investigated as negative electrode materials for Li-ion batteries using combinatorial and high-throughput techniques. X-ray diffraction and electron microprobe measurements were used to characterize the library structure. A large amorphous region exists in Si-rich compositions of this system. The electrochemistry of numerous compositions of Fe-Si-Zn materials was determined near room temperature. Both Zn and Fe additions to Si were found to suppress the formation of Li15 Si4 during cycling.